2021
DOI: 10.1002/glia.24126
|View full text |Cite
|
Sign up to set email alerts
|

Id2 and Id4 are not the major negative regulators of oligodendrocyte differentiation during early central nervous system development

Abstract: Myelin sheathes ensure the rapid conduction of neural impulse and provide nutritional support for neurons. Myelin sheathes are formed by differentiated oligodendrocytes (OLs) in the central nervous system. During OL development, the differentiation of oligodendrocyte progenitor cells (OPCs) into mature OLs is controlled by both positive differentiation factors (drivers) and negative regulatory factors (brakes). Previous studies have suggested Id2 and Id4 as the key negative factors for OL differentiation. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has been proposed that the inhibitory effects of GPR17 on OPC maturation are, at least partially, due to the upregulation and nuclear translocation of ID2/ID4, the potent OL differentiation inhibitors (Chen et al, 2009; Wang et al, 2001). However, a recent study demonstrated that ID2/ID4 are not expressed in OPCs during normal CNS development, and genetic disruption of both ID2 and ID4 has no or little effect on OPC generation and differentiation (Huang et al, 2022). Therefore, the precise function of GPR17 in OPC lineage progression and its working mechanism are still somewhat controversial and remain to be further clarified.…”
Section: Transcriptomic Signatures Of Copsmentioning
confidence: 99%
“…It has been proposed that the inhibitory effects of GPR17 on OPC maturation are, at least partially, due to the upregulation and nuclear translocation of ID2/ID4, the potent OL differentiation inhibitors (Chen et al, 2009; Wang et al, 2001). However, a recent study demonstrated that ID2/ID4 are not expressed in OPCs during normal CNS development, and genetic disruption of both ID2 and ID4 has no or little effect on OPC generation and differentiation (Huang et al, 2022). Therefore, the precise function of GPR17 in OPC lineage progression and its working mechanism are still somewhat controversial and remain to be further clarified.…”
Section: Transcriptomic Signatures Of Copsmentioning
confidence: 99%
“…G protein-coupled receptor 17 (GPR17) can act as a downregulator of OLIG1 that negatively controls the maturation and coordinates the generation of myelinating OLs from pre-myelinating OLs through ID proteins [ 113 ]. Although overexpression of ID2 and ID4 both regulate myelin gene expression by inhibiting OLs differentiation [ 89 , 114 ], they are not the major in vivo repressors of differentiation [ 115 ]. Moreover, decreased levels of OLIG1 and myelin regulatory factor (MYRF) were observed under early growth response 1 (EGR1) and SOX11 overexpression, delineating the inhibitory action of the latest in OPCs differentiation [ 116 , 117 ].…”
Section: Myelinogenesis and Myelin Development: A Spatiotemporal Coor...mentioning
confidence: 99%
“…In the central nervous system (CNS), myelin sheaths, the major component of the white matter, are elaborated by mature oligodendrocytes (OLs). Myelin plays a crucial role in the rapid and precise conduction of action potentials [ 1 , 2 , 3 , 4 ]. Increasing evidence has demonstrated that abnormal myelin development contributes to the disease pathogenesis including Alzheimer’s disease, major depression, and schizophrenia [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%